Sistem Papan Monitoring Penggunaan Kelas dan Peralatan Elektronik Terintegrasi Internet of Things (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2023)
One of the most influential uses of technology today is the use of the Internet of Things (IoT). In this development, it has a special impact on the field of monitoring system, one of which is to monitor classrooms. Generally, the problem that often occurs in the use of classrooms as a means of learning is due to the negligence of users who forget to turn off electronic equipment that has been used when teaching learning activities are completed. For this reason, a system can control or control electronic equipment contained in the classroom remotely, and can monitor or monitor the activity in the classroom.